Ujaran Kebencian Masyarakat Kota Kendari di Media Sosial - Gunawan, Fahmi (Institut Agama Islam Negeri Kendari, 2020)
The purpose of this study is to examine Kendari community's hate speech on social media. This study employed a qualitative research paradigm in conjunction with a case study approach. Data were gathered through in-depth interviews, focus groups discussions, and the distribution of questionnaires. To ascertain the forms and meanings of Southeast Sulawesi people's hate speech on social media, in-depth interviews and focus group discussions were undertaken. The questionnaire was administered in order to ascertain the elements that contributed to the rise of hate speech. Sampling was conducted using either theoretical sampling or purposive sampling. The findings indicated that the inhabitants of Southeast Sulawesi engage in five distinct types of hate speech, namely (1) defamation, (2) insults, (3) blasphemy, (4) instigation, and (5) disseminating hoaxes. There are two types of causes that contribute to hate speech: internal and external. Internal causes include hurt and fashion, but external factors include political interests, group interests, and ethnicity, religion and race interest.